Proportion of Oatmeal and Gambir Masks as an Aging Facial Skin Care - KAMILIA, NAZHIFAH TASYA; Rosalina, Linda (JURNAL PENDIDIKAN DAN KELUARGA; Vol 15 No 01 (2023): Jurnal Pendidikan dan KeluargaDO - 10.24036/jpk/vol15-iss01/1116, 2023)
Skin aging is a phenomenon of decreasing the size, number of skin cells and changes in the organic function of the skin caused by a process of deterioration of the skin structure and a decrease in normal skin function. This study aims to make cosmetic face masks for the care of aging facial skin using a mixture of oatmeal and gambir ingredients. This research uses an experimental method with a quantitative descriptive approach. The types of data sources used are primary data and data collection techniques using observation and documentation methods. This study used organoleptic tests (texture, aroma, adhesion), hedonic tests (panelists' preferences) and laboratory tests. The panelists used consisted of 7 people. The proportion of oatmeal and gambir masks used is 20:80, 30:70 and 40:60. In the organoleptic test, the highest texture was found in the ratio of 20:80, in the highest aroma test it was found in the comparison of 20:80 and in the highest adhesion test it was found in the ratio of 20:80 and 30:70. Meanwhile, the highest hedonic test results (panelists' preferences) are found in a ratio of 30:70. In the results of laboratory tests on the proportion of masks of 30:70, there was a content of vitamin C as much as 11.66% and vitamin A as much as 0.26% in 100 gr of mask samples.